2014
DOI: 10.1371/journal.pone.0103944
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Food Influence Shell Growth and Mantle Gene Expression of Shell Matrix Proteins in the Pearl Oyster Pinctada margaritifera

Abstract: In this study, we analyzed the combined effect of microalgal concentration and temperature on the shell growth of the bivalve Pinctada margaritifera and the molecular mechanisms underlying this biomineralization process. Shell growth was measured after two months of rearing in experimental conditions, using calcein staining of the calcified structures. Molecular mechanisms were studied though the expression of 11 genes encoding proteins implicated in the biomineralization process, which was assessed in the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
77
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 42 publications
5
77
2
1
Order By: Relevance
“…Previous studies have shown that bivalve growth rate and its variability increase with temperature [32], reaching erratic values when temperature is too high [33]. Based on available data, it is difficult to determine whether the lower growth rates recorded in the cold season were solely due to lower temperatures, or if other season-related processes might be at play (e.g., lower irradiance).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that bivalve growth rate and its variability increase with temperature [32], reaching erratic values when temperature is too high [33]. Based on available data, it is difficult to determine whether the lower growth rates recorded in the cold season were solely due to lower temperatures, or if other season-related processes might be at play (e.g., lower irradiance).…”
Section: Discussionmentioning
confidence: 99%
“…The protein genes Pif-177 and MSI60 regulate growth, nucleation and the organization of the aragonite crystal 20, 22, 38 . Perline is the protein equivalent of the N14 protein identified in P. maxima 39 and seems to be specifically involved in the formation of the nacreous layer and promotion of aragonite crystal nucleation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, biotic factors affecting mollusk radial growth rates include: availability of nutrients (food), predation pressure, production of gametes, and spawning (Grave, 1911;Ivany, 2012;Joubert et al, 2014;Linard et al, 2011;Lowenstam and Weiner, 1989;Schöne, 2008). Abiotic factors include: temperature, salinity, lunar cycles and tides, seasonal variations (e.g., day length, storms), turbidity, ocean circulation patterns, sea level, and carbon (organic and inorganic), phosphate, and nitrate concentrations in the water column (Ivany, 2012;Joubert et al, 2014;Linard et al, 2011;Lowenstam and Weiner, 1989;Richardson et al, 1999;Schöne, 2008). Changes in growth rates are commonly detected in bivalves by the deposition of a growth line in the prismatic outer shell (Schöne, 2008).…”
mentioning
confidence: 99%
“…The most commonly investigated species are those of economic value in pearl aquaculture or human consumption, such as the pearl oyster (Pinctada margaritifera) or abalone (e.g., Haliotis refuscens). In these few studies, both temperature and nutrient concentrations were observed to impact rates of nacre deposition and total nacre thickness in tank experiments of P. margaritifera (Joubert et al, 2014;Linard et al, 2011). Additionally, different suites of genes have been identified in P. margaritifera that produce different regulatory proteins for prismatic (radial) vs. nacreous growth (Joubert et al, 2014;Marie et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation